Value Education in the Form of Bima Dompu Community Respectness - Suharyanto Soro (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aims to find the forms of respect used by the Bima Dompu community in their social interactions as the actualization of value education in the form of respect. In other words, applying the form of RESPECTS is the actualization of value education for the Bima Dompu community. The state of respectless in Indonesia language is called bentuk hormatan. Researchers used a qualitative approach (description). This approach describes phenomena or events that occur naturally. The methods used in this research were the observation and interview methods. Sampling was done by purposive sampling. The research location was in the Bima district, West Nusa Tenggara academic year 2020. The study’s findings indicated that the Bima Dompu community uses a form of RESPECTS to actualize educational values in their social interactions. Applying the importance of this form of RESPECTS has become a tradition and characteristic of those communities. An example of a state of RESPECTS (mention someone’s name) is if the person's name is Ahmad, becomes Hima for a nickname for people younger than that person. While the mention of a form of RESPECTS for the age and older than the age in calling still mentions the original name (Ahmad). This is a concrete form of teaching the values of politeness education passed down from generation to generation to create a nuance of harmony in society